Recent and Historical Gene Flow in Cultivars, Landraces, and a Wild Taxon of Cucurbita pepo in Mexico - Martínez-González, Carmina; Castellanos-Morales, Gabriela; Barrera-Redondo, Josué; Sánchez-de la Vega, Guillermo; Hernández-Rosales, Helena S.; Gasca-Pineda, Jaime; Aguirre-Planter, Erika; Moreno-Letelier, Alejandra; Escalante, Ana E.; Montes-Hernández, Salvador; Lira-Saade, Rafael; Eguiarte, Luis E. (Frontiers in Ecology and Evolution, 2021)
Gene flow among crops and their wild relatives is an active study area in evolutionary biology and horticulture, because genetic exchange between them may impact their evolutionary trajectories and increase the genetic variation of the cultivated lineages. Mexico is a center of diversity for the genus Cucurbita that includes pumpkins, squash and gourds. Gene flow between domesticated and wild species has been reported as common in Cucurbita; but gene flow among populations of C. pepo ssp. pepo from Mexico and its wild relative has not been studied. We used 2,061 SNPs, derived from tunable genotyping by sequencing (tGBS) to estimate gene flow among 14 Mexican traditional landraces of C. pepo ssp. pepo, also including individuals from five improved cultivars of C. pepo ssp. pepo and C. pepo ssp. ovifera var. ovifera, and individuals of their wild relative C. pepo ssp. fraterna. We found moderate to high levels of genetic diversity, and low to moderate genetic differentiation. In the test of introgression between lineages, we found that all possible arrangements for ancestral and derived sites between the lineages showed similar frequencies; thus, incomplete lineage sorting, but also gene flow, might be taking place in C. pepo. Overall, our results suggest that gene flow between these subspecies and cultigens, incomplete lineage sorting and the retention of ancestral characters shaped the evolutionary trajectory of C. pepo in its area of origin and diversification. In addition, we found evidence of the use of Mexican landraces as genetic material for the improvement of commercial cultivars. The landraces of Mexico are an important source of genetic diversity for C. pepo, which has been preserved both by management practices of small farmers and by the natural gene flow that exists between the different crop fields of the region.